Public–Private Partnerships: Strengthen Thailand’s Health Security in Confronting Emerging Infectious Diseases - Luangpaiboon, Pinsuda (Journal of Health Science of Thailand, 2017)
Infectious diseases are among the root causes of death and disability in an outbreak. As such, ensuring the development of adequate resources and access to healthcare services has become a priority for the national agenda. Governments across the world are increasingly turning to public-private partnerships as the primary mechanism for delivering healthcare services to meet this growing demand for national health security. The objective of this study was to explore the value of public health public-private partnerships project in strength-ening national pandemic influenza preparedness for Thailand. This study used the mixed research method to explore key public-private partnerships conducted for pandemic influenza preparedness, namely the Influenza Foundation of Thailand (IFT). The results revealed that the Influenza Foundation of Thailand aimed to create public health readiness for pandemic influenza preparedness. Both public and private participants were being driven together to accomplish Influenza Foundation of Thailand’s core objectives. The initiative provided public health facilities with the educational support needed as described in the national strategic plan by helping public organizations increase their capacity to deal with influenza disease outbreaks. Project effectiveness evaluation found that the effective training and education PPPs of Influenza Foundation of Thailand reflected not only the needs of pandemic influenza preparedness, but also the administrative capacity of a government in confronting emerging/re-emerging infectious diseases outbreaks in the future. The PPPs also served as the first step in creating an integrated national strategic agenda, given that PPPs were fundamental to the overall strategy of the nation.